2013
DOI: 10.4028/www.scientific.net/amm.302.550
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis for the Design of Branched Artificial Blood Vessel of Aortic Arch

Abstract: In order to set up a curved-shape branch artery-blood coupling model and investigate the effect of the material change in artificial blood vessel on the hemodynamic state, the method of finite element and Fluid Solid Interface in Ansys CFX was used to achieve the structural and fluid analysis with different materials. The displacement of tubular wall was increasing with the young's modulus decrease of material, and the tendency became clear. The von mises stress of the tubular wall is not well-distributed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Xuan et al [8] performed a fluid-structure interaction study of a simplified geometric model of the aortic arch and found that the wall shear stress was high in the inner wall of the middle portion of the aortic arch. Wang et al [9] performed a fluidstructure interaction study of an aorta modeled as a 180° curved pipe with only one branch. They found that the maximum values of von Mises stress occurs at the pipe inlet and the branch junction.…”
Section: Introductionmentioning
confidence: 99%
“…Xuan et al [8] performed a fluid-structure interaction study of a simplified geometric model of the aortic arch and found that the wall shear stress was high in the inner wall of the middle portion of the aortic arch. Wang et al [9] performed a fluidstructure interaction study of an aorta modeled as a 180° curved pipe with only one branch. They found that the maximum values of von Mises stress occurs at the pipe inlet and the branch junction.…”
Section: Introductionmentioning
confidence: 99%